Swot Analysis in The Medium-Term Work Plan at SMAN 1 Pagaden 2021-2025 - Gunawan Gunawan; Yulis Sunaryati (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
The Medium Term Work Plan (MTWP) in its preparation involves school supervisors, principals, school committees, teachers and other components involved in the school environment of SMAN 1 Pagaden. The purpose of preparing this MTWP is as a framework for all components at SMAN 1 Pagaden in four years. MTWP at SMAN 1 Pagaden is an effort to improve the quality of education such as curriculum development and improvement of advice and infrastructure, learning tools, management improvements, school funding and sources of funds, graduation standards, assessment systems and the role of school committees. Efforts to improve these things are by compiling the MTWP program for the period 2021-2025. This research was conducted to improve the performance or achievement of the work program of SMAN 1 Pagaden in period 2021–2025. This research was conducted at SMAN 1 Pagaden, Subang Regency, which took place from January to April 2021. The data was processed using the quality reports application published by the West Java education quality assurance institute as a measure of the achievement of the work program in the previous year. The data is processed and analyzed using the description method. The remedial/enrichment program so far has not been effective, it still uses the effective hours of teaching and learning. Improvements to the remedial/enrichment program aim to improve the quality of learning, with higher learning achievement expected to have an impact on the standard chart of content so that it can go to the national education standard 4 category. Strengthening remedial and enrichment programs can be optimized through the use of school operational assistance funds.